Evaluation and Analysis of Long-term Environmental Noise Levels in 7 Major Cities of India - GARG, Naveen; KUMAR, Saurabh; GAUTAM, Chitra; GANDHI, Vishal; GUPTA, Nalin Kumar (Archives of Acoustics, 2023)
This paper describes the long-term noise monitoring data for ten consecutive years (2011–2020) acquired from the diversified National Ambient Noise Monitoring Network (NANMN) set up across 7 major cities of India and consisting of 70 stations for continuous noise monitoring throughout the year. The annual average ambient noise levels observed throughout these ten years in 70 locations under study, including 25 locations in commercial zones, 12 in industrial, 16 in residential, and 17 in silence zones, are described. The noise scenario in these ten years is compared and analyzed. It is observed that no site in residential or silence zones meets the ambient noise limits for the past ten years. The study suggests guidelines for a policy framework for environmental noise management and control to regulate noise pollution in Indian cities.